Development of Open-Ended Based Learning Tools to Improve Creative Thinking and Self-Efficacy - Putri Elmaretha Purba; Elmanani Simamora; Izwita Dewi (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2022)
This study aims to: 1) obtain learning tools developed based on the Open-Ended approach using Hypercontent that meet validity, practicality and effectiveness to improve students' creative thinking skills and self-efficacy; 2) describe how the improvement of students' creative thinking skills and self-efficacy is implemented by using learning tools based on the Open-Ended approach using Hypercontent. This study uses the ADDIE development model. The results showed that 1) Learning tools based on the Open-Ended approach using hypercontent to improve the creative thinking skills and self-efficacy of SMK students that were developed had met the valid, practical and effective criteria; 2) Improved creative thinking skills and self-efficacy of SMK students using learning tools based on the Open-Ended approach using hypercontent which was developed on the material of sequences and series seen from the normalized gain index. It was found that the increase in students' creative thinking skills in the first try there was an increase in the score with the "low" criteria and in the second trial there was an increase in the score with the "medium" criteria, while the increase in students' self-efficacy was seen from the increase in the average value of the self-efficacy results from trial I to II.